Decoding airway granulogenesis in children: unveiling risk factors for tracheobronchial foreign body aspiration and complications - Yuting You; Meili Shen; Li’e Zeng; Jingyang Zheng (Italian Journal of Pediatrics, 2025)
Abstract Background Exogenous foreign body aspiration is a common high-risk condition in children. In a few cases, foreign body aspiration can lead to airway granulomas that interfere with tracheoscopic foreign body removal and threaten the life of the child. Methods This study was a retrospective analysis of the clinical data of 184 pediatric patients who were admitted to Quanzhou Children’s Hospital from 2018 to 2021 with exogenous tracheobronchial foreign bodies. Results Respiratory foreign bodies tend to occur during the winter and spring seasons. The solid foreign bodies were mostly nut foreign bodies, the location of implantation was the left lung rather than the right lung in many patients, and complications such as pulmonary atelectasis, emphysema, mediastinal and subcutaneous emphysema, and granulomatous tissue formation were noted in these patients. Statistical models suggested that the time of foreign body impaction and the release of oil were risk factors for tracheal granulation, with the logistic model presenting an AUC of 0.948, precision of 0.676, and sensitivity of 0.895, whereas the XGBoost model presented an AUC of 0.902, precision of 0.912, and sensitivity of 0.875. Conclusions Tracheobronchial foreign bodies primarily develop in male children under the age of 3 and often lead to various complications. The time of foreign body insertion and the release of oil from the obstructed foreign body have been identified as high-risk factors for the development of tracheobronchial granulation tissue. When the time of foreign body insertion without oil release exceeds 99.98 h or when the time of foreign body insertion with oil release exceeds 47.94 h, tracheobronchial granulation formation strongly suggests that the child is at high risk of developing airway granulation. In such cases, family members must implement increased supervision of the child to prevent choking. Medical professionals should obtain a detailed medical history of the affected child and accordingly select the most appropriate method to promptly remove the foreign body to resolve the issue of airway obstruction and reduce the likelihood of pulmonary complications in the child.